Awareness of cervical cancer, human papilloma virus (HPV) and HPV vaccination among women in a cancer screening, early diagnosis and education center (Annals of Medical Research, 2021)
Aim: This study was conducted to assess the awareness of women about cervical cancer and human papilloma virus (HPV) and to evaluate their HPV DNA test results.Materials and Methods: This analytical cross-sectional study was conducted in 250 women who applied to Cancer Early Diagnosis Screening and Training Center (KETEM) at Konya Training and Research Hospital of Health Sciences University. A questionnaire prepared by the researchers was applied to determine the women's sociodemographic characteristics, cervical cancer and HPV knowledge levels.Results: The mean age of the women was 47.7 ± 7.5 years old. When the smear results of the women included in the study are examined, HPV was positive in 3.2% (n=8). Participants with higher education levels had significantly higher Pap smear test knowledge and performed more Pap smear tests than those who had lower education levels (p
Keywords: Cervical cancer; early diagnosis of cancer; pap smear test; virus